The Connection of the Methodology of Teaching Foreign Languages with Other Sciences - Tadjibaeva Adila Ergashevna (Genius Journals, 2022)
In this article, the question of the connection of foreign language teaching methodology with other subjects was discussed. It was also researched that methodology has its own history due to the establishment of its status as a science. The connection of the methodology with linguistics, then with psychology, and finally with pedagogy or even with several other disciplines was noted
Keywords: Linguistics; foreign language teaching methodology; didactic principles; connection